Palliative cerebrospinal fluid shunting for leptomeningeal metastasis-related hydrocephalus in patients with lung adenocarcinoma: A single-center retrospective study - Mitsuya, Koichi (PLoS One, 2019)
PURPOSE: Management of leptomeningeal metastasis-related hydrocephalus (LM-H) is particularly challenging regarding the control of severe headache, nausea, and vomiting due to intracranial hypertension. To investigate the improvements of performance status and outcome with cerebrospinal fluid (CSF) shunt surgery for LM-H in patients with lung adenocarcinoma. METHODS: Data on patients with leptomeningeal metastasis-related hydrocephalus from lung adenocarcinoma diagnosed by MR imaging and/or cytological examination were retrospectively analyzed. Between August 2008 and July 2017, the authors reviewed 31 patients requiring CSF shunt, who underwent ventriculo-peritoneal or lumbo-peritoneal shunt. RESULTS: The patients consisted of 11 men and 20 women with a median age of 59 years. Twenty-six patients received EGFR-tyrosine kinase inhibitors (TKIs). CSF shunt surgery yielded rapid improvement in the performance status of 90.3% of patients. Median overall survival from the diagnosis of LM in patients with ECOG performance status less than 2 was 7.7 months, and this was significantly longer than those in patients with PS 3 or 4 (4.4 or 1.5 months; p<0.001). Multivariate analysis by Cox regression revealed survival differences according to PS at diagnosis of LM [PS 1–3 vs. PS4, hazard ratio (HR) 0.201, p = 0.034], controlled extracranial disease (HR 0.248, p = 0.005), and post-shunt EGFR-TKI for LM treatment (HR 0.193, p = 0.008). Postoperative symptomatic peritoneal carcinomatosis was observed in one patient (3.2%). CONCLUSION: CSF shunting may be a safe and effective strategy in patients with LM-H from lung adenocarcinoma. A prospective study is needed to establish the effectiveness and safety of palliative CSF shunt for LM-H.